2017
DOI: 10.1177/1948550617728993
|View full text |Cite
|
Sign up to set email alerts
|

Equality Revisited: A Cultural Meta-Analysis of Intergroup Contact and Prejudice

Abstract: Across cultures, intergroup contact-interpersonal interaction with out-group members-is associated with less prejudice. Contact research was criticized, however, for bypassing intergroup inequality in the wider society. We propose a cultural psychology approach grounding people's contact experiences in culturally afforded ways of relating to out-groups. Extending Allport's equal-status hypothesis to the culture level, we hypothesized that the contact-prejudice association would be stronger in egalitarian cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 32 publications
5
59
0
4
Order By: Relevance
“…We are also cautious to interpret our findings in the light of recent evidence for a caveat in the contact‐prejudice link. Kende and colleagues () recently reconducted the meta‐analysis of Pettigrew and Tropp () by adding cultural level variables. Although they replicated the findings that contact predicted weaker prejudice in most countries, this effect depended on the extent to which a culture was egalitarian or hierarchical.…”
Section: Discussionmentioning
confidence: 99%
“…We are also cautious to interpret our findings in the light of recent evidence for a caveat in the contact‐prejudice link. Kende and colleagues () recently reconducted the meta‐analysis of Pettigrew and Tropp () by adding cultural level variables. Although they replicated the findings that contact predicted weaker prejudice in most countries, this effect depended on the extent to which a culture was egalitarian or hierarchical.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a dimension of complexity, recent research has considered intergroup context as an indicator of ideology. Noting that some cultures are generally more egalitarian (e.g., the Netherlands), whereas others are more hierarchical (e.g., India), Kende, Phalet, Vanden Noortgate, Kara, and Fischer (2018) reanalyzed Pettigrew and Tropp's (2006) contact meta‐analysis after coding for country‐level egalitarianism. In contrast to what is commonly found at the individual level, at a societal level Kende et al found that contact reduces prejudice more in egalitarian than in hierarchical societies.…”
Section: Future Directionsmentioning
confidence: 99%
“…In sociology, the “contact hypothesis” has been employed for over 60 years as means of explaining how attitudes and behaviors can change as a consequence of long‐term meaningful (equal‐status, nontransactional) interaction between groups of distinct interest/origin. While this notion was originally developed in the context of racial prejudice reduction in the United States of the mid‐20th century (Allport, ), decades of further study has validated its prediction that under circumstances of prolonged equal‐status co‐existence and interaction, common experience will shape and sway the opinions and worldview of even the most entrenched actors (Kende, Phalet, Van den Noortgate, Kara, & Fischer, ; Mirwaldt, ; Pettigrew & Tropp, ; Pettigrew, Tropp, Wagner, & Christ, ). When these interactions extend beyond the transactional, to the kinds of more profound egalitarian relationships that emerge when diverse individuals interact and coexist for long periods of times while engaged in mutually‐beneficial activities, individuals begin to exhibit real social and cultural exchange, and new and hybrid behaviors emerge.…”
Section: Discussionmentioning
confidence: 99%